Stability analysis of ginger (Zingiber officinale Rose.) genotypes - Mayadevi, K C Aipe, K Kumaran, T P Manomohan Das, T Pradeepkumar, P (Journal of Spices and Aromatic Crops, 2000)
Ten genotypes of ginger (Zingiber officinale) were subjected to stability analysis based on their evaluation for 6 years at Regional Agricultural Research Station, Ambalavayal (Kerala, India). All the genotypes differed significantly for tiller number, leaf number and yield. Stability analysis revealed the superiority. of Ernadan and Kuruppampady as they expressed high mean yield, non significant S2di values and a regression nearing unity.